A survey of retention practices and protocols followed among orthodontists in India - S R Radha; Gowri Sankar Singaraju; Prasad Mandava; Vivek Reddy Ganugapanta; Hema Bapireddy; Lakshmi Narayana Pilli (Wolters Kluwer Medknow Publications, 2021)
Background: There are different types of retention protocols and retainers prescribed by the orthodontists across the globe. Aim: The study was conducted with the aim of evaluating the retention practices followed by the orthodontists in India. Materials and Methods: A questionnaire link with a set of 29 questions was generated using the Google Forms App. The questions related to the basic demographic details followed by retention procedures in maxilla and mandible as related to the type of retainer, duration of wear, retention check-ups, and adjunctive procedures being followed. The Google forms were mailed to 1147 registered life members of the Indian Orthodontic Society. Results: The overall response rate was 20.1%. On receiving of the completed questionnaires, the data were statistically analyzed. Dual mode of retention, fixed retainers with removable thermoplastic resin (TR)/vacuum formed retainers (VFR) (24%) were the common type of retention in maxilla whereas the fixed bonded retainer (44.5%) was more commonly used in mandible. Full time wear of maxillary retainer was recommended by 85.2% of the respondents. The recommended duration of the fixed retainer is for 2-5 years (41.9%). Conclusion: A trend towards more dual retention instead of solitary removable or solitary fixed retention, more VFR instead of Hawley-type retainers has been demonstrated in the survey.